Digital Education on Knowledge of Ultra-Processed Foods in Grade XI Adolescents - Srimiati, Mia; Ratnayani, Ratnayani (Jurnal Abmas Negeri (JAGRI), 2025)
Adolescents represent a critical age group in the formation of lifestyle habits, including dietary patterns. This community service program aimed to improve adolescents’ understanding of ultra-processed foods (UPF) through interactive digital education. The main issue faced by the partner school was students’ limited knowledge of the health impacts of UPF consumption, largely due to the widespread availability of fast food in the school environment. The intervention employed a hybrid approach combining face-to-face and online activities at SMK Bina Pangudi Luhur Jakarta, involving 27 eleventh-grade students. Educational methods included lectures, interactive discussions, and educational games using PowerPoint, Instagram, and Kahoot. Evaluation using pre- and post-tests showed a significant increase in knowledge (p-value = 0,001), indicating that digital education was effective in enhancing adolescents’ nutrition literacy and awareness regarding UPF.